PENGARUH CORPORATE GOVERNANCE, KARAKTER EKSEKUTIF, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) (Studi Pada Perusahaan Pertanian dan Pertambangan yang Terdaftar di BEI Tahun 2011-2014) - Khoirunnisa Alviyani; Raja Adri Satriawan Surya; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine the effect of corporate governance, excecutive characters, firm size, and leverage on the extent of tax avoidance with proxy book tax gap. The population in this study is the Registered Agriculture and Minning companies in Indonesia Stock Exchange in 2011 until 2014. The sample was determined by the purposive sampling method and obtain 12 companies. Type of data used was secondary data obtained from www.idx.co.id or corporate websites. The method of analysis used is multiple regression analysis. The results of study show that institusional ownership has significant effect on tax avoidance, where the significant value are 0,045<0,05. Quality auditte has significant effect on tax avoidance, where the significant value are 0,371>0,05. Independent commisaries has a significant effect on tax avoidance, where the significant value are 0,000<0,05. Audit commite has no significant effect on tax avoidance, where the significant value are 0,459>0,05. Exchecutive charachters has signifikan effect on tax avoidance, where the significant value are 0,010<0,05. Firm size has significant effect on tax avoidance, where the significant value are 0,000<0,05. Leverage has no significant effect on tax avoidance, where the significant value are 0,490>0,05.Keywords: corporate governance, exchecutive charachters, firm size, leverage, and tax avoidance.